Creditors in Control: The Exercise of Creditors of Corporate Control through Loan Agreements - Jumamil, Theodore Joseph M. (Diliman, Quezon City, Philippines: University of the Philippines College of Law)
The 1987 Constitution espouses a simple economic philosophy: "[t]he State shall develop a self-reliant economy effectively controlled by Filipinos. " As operationalized in Philippine laws and jurisprudence, this constitutional command is premised upon the presumption that "control" can only be exercised through "capital". Thus, the current regulatory framework focuses on control exercised through voting stock, securities, or other complex transactions. In reality, however, innovations and advances in finance and contract law are eroding the traditional notion that control is exercised through "capital". It is possible for corporate control to be exercised through debt instruments. A litany of ways exist through which creditors can exercise control over corporate decision-making. The differences in method lie in who exercises the control-mechanisms, how the mechanisms are exercised, and when they are exercised. Do these transactions undermined the constitutional policy granting control of corporations engaged in nationalized and partially nationalized activities to Filipino nationals? Are there other complex debt transactions that permit its circumvention? Does the current regulatory regime render them illegal? If not, what regulatory measures should be introduced to address their use?
Keywords: Corporation law